Եգիպտոսի ղպտիները 2011թ.-ի հունվարի 25-ի հեղափոխության և բարձրագույն զինվորական խորհրդի կառավարման շրջանում (փետրվար 11, 2011 - 30 հունիս, 2012) - Անտոնյան, Աննա («Զանգակ - 97»)
This article analyzes the position of the Copts,indigenous Egyptian Christians, on the Egyptian Revolution of the 25January 2011, which took place as a solid outcome of the “Arab spring” in Egypt, and important events that took place in the country under the rule of the Supreme Military Council (February 11, 2011 . - June 30, 2012). The Copts, after almost a century of passivity, took advantage of the situation and tried to return to the socio-political arena, putting forward their concerns not only with the help of the Coptic Orthodox Church, but also by establishing secular structures and using the tools of street and Internet struggle. Some aspects of discriminatory policies against Copts in the period under study are analyzed in the article. The article also examines the existing relations between the Coptic Orthodox Church and the state, as well as the attitude of the church to the processes of the “Arab Spring”.
Keywords: Պատմություն; Համաարաբական ըմբոստություն